Experimental particle formation rates spanning tropospheric sulfuric acid and ammonia abundances, ion production rates, and temperatures. Issue 20 (27th October 2016) - Kürten, Andreas; Bianchi, Federico; Almeida, Joao; Kupiainen‐Määttä, Oona; Dunne, Eimear M.; Duplissy, Jonathan; Williamson, Christina; Barmet, Peter; Breitenlechner, Martin; Dommen, Josef; Donahue, Neil M.; Flagan, Richard C.; et al.
Abstract: Binary nucleation of sulfuric acid and water as well as ternary nucleation involving ammonia are thought to be the dominant processes responsible for new particle formation (NPF) in the cold temperatures of the middle and upper troposphere. Ions are also thought to be important for particle nucleation in these regions. However, global models presently lack experimentally measured NPF rates under controlled laboratory conditions and so at present must rely on theoretical or empirical parameterizations. Here with data obtained in the European Organization for Nuclear Research CLOUD (Cosmics Leaving OUtdoor Droplets) chamber, we present the first experimental survey of NPF rates spanning free tropospheric conditions. The conditions during nucleation cover a temperature range from 208 to 298 K, sulfuric acid concentrations between 5 × 10 5 and 1 × 10 9  cm −3, and ammonia mixing ratios from zero added ammonia, i.e., nominally pure binary, to a maximum of ~1400 parts per trillion by volume (pptv). We performed nucleation studies under pure neutral conditions with zero ions being present in the chamber and at ionization rates of up to 75 ion pairs cm −3  s −1 to study neutral and ion‐induced nucleation. We found that the contribution from ion‐induced nucleation is small at temperatures between 208 and 248 K when ammonia is present at several pptv or higher. However, the presence of charges significantly enhances the nucleation rates, especially at 248 K with zero added ammonia, and for higher temperatures independent of NH3 levels. We compare these experimental data with calculated cluster formation rates from the Atmospheric Cluster Dynamics Code with cluster evaporation rates obtained from quantum chemistry. Key Points: First experimental survey of new particle formation rates spanning free tropospheric conditions Addition of NH3 in the low pptv‐range strongly enhances new particle formation at low temperature Ion‐induced nucleation is most efficient at temperatures of 248 K and higher